Advanced Numerical Evaluation of the Jet Fire Caused by Accidental Releases of Liquid Hydrogen - Gianmaria Pio; Ernesto Salzano; Alessandro Tugnoli (Chemical Engineering Transactions)
Considering the ongoing energy transition and the role of hydrogen within the process, a complete and comprehensive understanding of the safety aspects of hydrogen storage technologies is paramount to guarantee the sustainable development of these alternative solutions at an industrial scale. Among the available storage conditions, the possibility of using cryogenic temperatures to liquefy hydrogen has become more credible also due to the knowledge gained by the use of liquefied natural gas. Nevertheless, the peculiar properties of hydrogen promote dedicated analysis of the safety aspects. For these reasons, the current work presents an advanced numerical investigation on the jet fires deriving from the accidental release of liquid hydrogen, performed employing the open-source software Open Field Operation and Manipulation (OpenFOAM). Considering the dearth of experimental data at the boundary conditions of interest, preliminary investigations were carried out to assess the suitability of the existing sub-models and parameters for the evaluation of hydrogen jet fire caused by an accidental release from high pressure and atmospheric temperature. A maximum temperature of ~ 2300 K was observed within the core of the flame. The locations where the maximum temperatures were observed are in line with experimental data available in the current literature, confirming the validity of the implemented models for the evaluation of near-field fluid dynamics and overall chemistry. In addition, the case of a non-ignited release was also analyzed in terms of temporal and spatial profiles of temperature and hydrogen content within the numerical domain. Based on the gathered information, the maximum distance between the releasing point and the edge of the flammable cloud was obtained as a function of the releasing conditions. In conclusion, the availability of robust and validated models for the characterization of the accidental releases of liquid hydrogen paves the way for further development and wider adoption of this technology as well as the optimized design of mitigation systems and safety procedures.